Corrections to Phytotaxa 222: Some nomenclatural adjustments and typifications for almond species in the genus Prunus sensu lato (Rosaceae) - Eisenman, Sasha William (Phytotaxa, 2015)
Following the publication of Some nomenclatural adjustments and typifications for almond species in the genus Prunus sensu lato (Rosaceae) (Eisenman 2015), two necessary corrections were brought to my attention.